2006
DOI: 10.1186/1471-2334-6-39
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea, CD4 counts and enteric infections in a hospital – based cohort of HIV-infected patients around Varanasi, India

Abstract: Background: As most of the studies in HIV patients with diarrhea were cross sectional, focusing on the etiological agents, we are reporting data on the rate of diarrhea, associations between diarrhea and CD4 counts and variation in frequency of identifying a pathogen with consistency of diarrhea and duration in a prospective hospital based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 14 publications
8
46
2
1
Order By: Relevance
“…In this study it was observed that most of the diarrhoea cases were due to pathogens, which correlates with results found elsewhere [19,20]. Therefore, apart from the effects of HIV enteropathy, the presence of intestinal parasites is an important contributing factor to diarrhoea, which in the longer term could result in the wasting syndrome called "slim disease" [3,21].…”
Section: Discussionsupporting
confidence: 71%
“…In this study it was observed that most of the diarrhoea cases were due to pathogens, which correlates with results found elsewhere [19,20]. Therefore, apart from the effects of HIV enteropathy, the presence of intestinal parasites is an important contributing factor to diarrhoea, which in the longer term could result in the wasting syndrome called "slim disease" [3,21].…”
Section: Discussionsupporting
confidence: 71%
“…Factors associated with intestinal parasitic infections (multiple-regression analysis) participants with lower CD4 T-cell counts. Higher prevalence of diarrhoea in association with lower CD4 T-cell counts has been reported by several studies [10,[19][20][21][22]. A recent study from Denmark has also reported diarrhoea as a common symptom in HIVinfected individuals; however, it emphasized that the diarrhoea is not associated with lower CD4 T-cell count or the presence of intestinal parasites [23].…”
Section: Discussionmentioning
confidence: 83%
“…However, it has been reported that the diagnostic yield of the stool analysis is low in patients with higher CD 4 + counts. It has also been suggested that HAART helps in eradicating opportunistic protozoal infections and that it is associated with the influx of CD 4 + cells into the lamina propria [24].…”
Section: Discussionmentioning
confidence: 99%